2022
DOI: 10.3390/diagnostics12123078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Macular Thickness Changes after Uncomplicated Phacoemulsification Surgery in Healthy Subjects and Diabetic Patients without Retinopathy by Spectral Domain OCT

Abstract: Purpose: To assess differences in the evolution of macular thickness after uncomplicated phacoemulsification surgery between non-diabetic subjects and patients with diabetes mellitus (DM) without diabetic retinopathy (DR), using Spectral Domain OCT (SD-OCT). Methods: We performed a unicentric prospective study including one hundred and thirty-one eyes of 70 patients divided into two groups—34 well-controlled DM patients without DR and 36 non-diabetic subjects—who underwent phacoemulsification for cataract surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In this study, only patients with diabetic retinopathy were excluded, while patients with diabetes mellitus (DM) were not excluded. Segura et al [ 33 ] conducted a study comparing macular thickness changes after uncomplicated phacoemulsification surgery, featuring two groups: a DM group without diabetic retinopathy and a non-DM group. The authors found increased macular thickness in both groups, yet discerned no significant differences between them.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only patients with diabetic retinopathy were excluded, while patients with diabetes mellitus (DM) were not excluded. Segura et al [ 33 ] conducted a study comparing macular thickness changes after uncomplicated phacoemulsification surgery, featuring two groups: a DM group without diabetic retinopathy and a non-DM group. The authors found increased macular thickness in both groups, yet discerned no significant differences between them.…”
Section: Discussionmentioning
confidence: 99%
“…A recently demonstrated risk factor is a central macular thickness >260. 5 µm measured with OCT before cataract surgery, which increases the probability of developing intraretinal cysts by 9.08 times [6]. Some studies have demonstrated that alterations of the ganglion cell layer thickness (GCLT), inner nuclear layer (INL), and Muller cells layer are produced in PCME with posterior GCL atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically significant PCME can lead to visual acuity impairment and morphologic alterations in OCT; its incidence in the last decade has ranged from 0.02 to 4.2% after uncomplicated phacoemulsification [ 4 ]. Macular thickness increases up to 6 months after uncomplicated cataract surgery in both diabetes mellitus (DM) patients without diabetic retinopathy (DR) and non-diabetic subjects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%